RSPO3 impacts body fat distribution and regulates adipose cell biology in vitro - Nellie Y. Loh (Nature Portfolio, 2020)
Genetic variants at the RSPO3 locus are associated with waist-to-hip ratio (adjusted for BMI). Here, Loh et al. describe two independent RSPO3 signals that associate with body fat distribution, perform fine-mapping and explore the function of RSPO3 in human adipocyte biology and body fat distribution in zebrafish